Tag along - Ryan, Tom, 1977 February 26- (Orca Book Publishers, 2013)
"It's junior prom night. Andrea is grounded for getting her older brother to buy booze for her, Paul is having panic attacks, Roemi has been stood up by his Internet date, and Candace is busy tagging a building (before she gets collared by a particularly tenacious cop). By happenstance, the four near-strangers end up together, getting into more trouble, arguing and ultimately helping each other out over the course of eight madcap hours."--